Induction versus progression of brain tumor development: differential functions for the pRB- and p53-targeting domains of simian virus 40 T antigen. - Sáenz Robles, M T (1994)
The ability of simian virus 40-encoded large T antigen to disrupt the growth control of a variety of cell types is related to its ability to interfere with certain cellular proteins, such as p53 and the retinoblastoma susceptibility gene product (pRB). We have used wild-type and mutant forms of T antigen in transgenic mice to dissect the roles of pRB, p53, and other cellular proteins in tumorigenesis of different cell types. In this study, using a cell-specific promoter to target expression specifically to brain epithelium (the choroid plexus) and to B and T lymphoid cells, we characterize the tumorigenic capacity of a T-antigen fragment that comprises only the amino-terminal 121 residues. This fragment (dl1137) retains the ability to interact with pRB and p107 but lacks the p53-binding domain. While loss of the p53-binding region results in loss of the capacity to induce lymphoid abnormalities, dl1137 retains the ability to induce choroid plexus tumors that are histologically indistinguishable from those induced by wild-type T antigen. Tumors induced by dl1137 develop much more slowly, however, reaching an end point at around 8 months of age rather than at 1 to 2 months. Analysis of tumor progression indicates that tumor induction by dl1137 does not require secondary genetic or epigenetic events. Rather, the tumor growth rate is significantly slowed, indicating that the T-antigen C-terminal region contributes to tumor progression in this cell type. In contrast, the pRB-binding region appears essential for tumorigenesis as mutation of residue 107, known to disrupt pRB and p107 binding to wild-type T antigen, abolishes the ability of the dl1137 protein to induce growth abnormalities in the brain.